Multicolor pattern scan laser for diabetic retinopathy with cataract - Hirano, Takao (International Journal of Ophthalmology Press, 2014)
AIM: To evaluate the ability of various laser wavelengths in delivering sufficient burns to the retina in eyes with cataract using a new multicolor pattern scan laser with green (532 nm), yellow (577 nm), and red (647 nm) lasers. METHODS: The relationship between the Emery-Little (EL) degree of cataract severity and the laser wavelength required to deliver adequate burns was investigated in 102 diabetic eyes. Treatment time, total number of laser shots, and intra-operative pain were assessed as well. RESULTS: All EL-1 grade eyes and 50% of EL-2 eyes were successfully treated with the green laser, while 50% of EL-2 eyes, 96% of EL-3 eyes, and 50% of EL-4 eyes required the yellow laser. The red laser was effective in the remaining 4% of EL-3 and 50% of EL-4 eyes. CONCLUSION: Longer wavelength lasers are more effective in delivering laser burns through cataract when we use a multicolor pattern scan laser system.